2022
DOI: 10.1177/17562872221097345
|View full text |Cite
|
Sign up to set email alerts
|

Role of low- versus high-power laser in the treatment of lower pole stones: prospective non-randomized outcomes from a university teaching hospital

Abstract: Introduction: Ureteroscopy and laser stone fragmentation [flexible ureteroscopy and laser lithotripsy (FURSL)] has risen over the last two decades. Laser technology has also evolved over the time, shifting from low- to high-power lasers with the addition of MOSES technology that allows for ‘dusting and pop-dusting’ of stones. The aim of the study was to look at the outcomes of FURSL in lower pole stones (LPS) using low- and high-power lasers. Patient and Methods: In this study, we compared the outcomes of low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…In addition, patients who used HPL had lower operation time, hospital stay, and uoroscopy time than the LPL group. Previous studies comparing HPL and LPL reported similar SFR at both laser powers [5][6][7]. Furthermore, SFR was similar for the rst and postoperative third months at different energies.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In addition, patients who used HPL had lower operation time, hospital stay, and uoroscopy time than the LPL group. Previous studies comparing HPL and LPL reported similar SFR at both laser powers [5][6][7]. Furthermore, SFR was similar for the rst and postoperative third months at different energies.…”
Section: Discussionsupporting
confidence: 56%
“…Our study reports postoperative complications according to the Clavien-Dindo grading [11] [12]. In the literature comparing HPL and LPL as complications, the complication rates were changing between 4.3-21% vs. 4.7-17.7% for HPL and LPL, respectively (5,6,8); it was 22.9% − 18.2% for HPL and LPL in our study, and no difference was found in terms of complications between the groups. Although serum creatinine measurement is nonspeci c, it indirectly indicates tubular damage, and preoperative and postoperative creatinine values and kidney damage markers were considered [13] [14].…”
Section: Discussionmentioning
confidence: 43%
“…The complication comparison between MOSES mode and normal mode comprised data from 6 studies (with 779 patients) [ 12 14 , 16 – 18 ]. In relation to safety, no significant difference was found in the forest plot (RR = 0.85, 95% CI 0.48–1.53, P = 0.806, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One advantage is that smaller laser fibre sizes that might be used with TFLs, coupled with the new miniaturized technologies and the smaller single-use flexible scopes, might extend the use of RIRS for larger and lower pole stones. Additionally, high-power lasers might widen the horizon of RIRS, since some studies have already demonstrated advantages in terms of shorter operative time, reduced use of ureteral access sheath (UAS), and postoperative stent, which in turn mean a reduction in sepsis-related complication rates [102]. Large comparative studies comparing TFL and Ho:YAG lasers with MOSES technology might shed new light on what the best treatment is in terms of surgical outcomes, emphasizing the outcome measures such as stone-free rate and the imaging used to achieve it, quality of life, costs, and environmental impact [103][104][105].…”
Section: Future Perspectivesmentioning
confidence: 99%